Climate modes of the phanerozoic : the history of the earth's climate over the past 600 million years - 324966 Frakes, Lawrence A; Francis, Jane E.; Syktus, Jozef I. (New York, N.Y., USA : Cambridge University Press, 1992)
Includes bibliographical references (p. 220-270) and index